2021
DOI: 10.3389/fonc.2020.508126
|View full text |Cite
|
Sign up to set email alerts
|

Hypercholesterolemia Is an Associated Factor for Risk of Differentiated Thyroid Cancer in Chinese Population

Abstract: BackgroundHyperlipidemia has been hypothesized as a risk factor for thyroid cancer. However, the association between hypercholesterolemia and thyroid cancer is unclear, especially in Chinese population without available published data. We conducted this study to investigate the relationship between hypercholesterolemia and differentiated thyroid cancer (DTC) in Chinese population.MethodsThree thousand seven hundred forty-eight patients were enrolled in the study, including 2,021 DTC patients and 1,727 benign s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
3
5
0
Order By: Relevance
“…Corroborating our study, the three cohort studies all showed an association between a lower level of HDL-C and a higher risk of thyroid cancer [8,11,29]. Among the cross-sectional or case-control studies, a lower level of HDL-C was reported among cases of thyroid cancer, compared to controls, in four studies [10,18,20,21], although not all differences were statistically significant. However, no difference was noted between cases and controls in the other five studies [13,15,22,24,25].…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Corroborating our study, the three cohort studies all showed an association between a lower level of HDL-C and a higher risk of thyroid cancer [8,11,29]. Among the cross-sectional or case-control studies, a lower level of HDL-C was reported among cases of thyroid cancer, compared to controls, in four studies [10,18,20,21], although not all differences were statistically significant. However, no difference was noted between cases and controls in the other five studies [13,15,22,24,25].…”
Section: Discussionsupporting
confidence: 71%
“…The cohort study did not find a statistically significant association between per quintile increase in TC and risk of thyroid cancer among either men or women [17]. Among the cross-sectional or case-control studies, six reported a lower level of TC [14,18,20,21,24,25], whereas three reported a similar or higher level of TC [16,22,26] among cases with thyroid cancer, compared to controls. Some of the studies [18,22,25,26] were relatively small, making random finding a potential concern.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Dyslipidemia has become the leading modifiable risk factor for CVD and has detrimental effects on certain types of cancer risk as well as prognosis (7)(8)(9)(10)(11). Thyroid hormones play a major role in lipid metabolism, and many studies have found relationships between thyroid diseases and lipids.…”
Section: Introductionmentioning
confidence: 99%